Long-term multi-objective distribution network planning by DG allocation and feeders’ reconfiguration - Zidan, Aboelsood; Shaaban, Mostafa F.; El-Saadany, Ehab F. (Electric power systems research, 2013)
•This paper proposes multi-year joint reconfiguration and DG allocation method.•Two objectives are considered: minimal cost and minimal gas emissions.•Impacts of uncertainty of renewable DG units and load variation are considered.•Different types of DGs and load growth across the planning horizon are considered. This paper proposes a long-term planning method to maximize the benefits of network reconfiguration and distributed generation (DG) allocation in distribution networks. The proposed method handles long-term yearly load increase and seeks to define the reinforcements (i.e., line upgrades, network reconfiguration, and DG integration) and when and where they are required to meet the load rise with minimal cost and acceptable quality standards. The objectives considered in this paper are: economic (costs of line upgrades, energy losses, switching operations, and DG capital, operation and maintenance costs) and environmental (emissions from grid and DG units). The proposed method takes into consideration the uncertainty related to renewable DG output power and the load variability. The long-term planning problem is defined as multi-objective nonlinear mixed integer programming. The outcomes of the planning problem are the Pareto front, which represents different optimum operating system points. Finally, the local distribution company (LDC) can choose the system operating point based on its preferences.